2024
DOI: 10.1371/journal.pone.0295394
|View full text |Cite
|
Sign up to set email alerts
|

‘There was a pivotal moment’. The dynamics, transitions, adaptations and trajectories of nursing at the front-line in the UK during the COVID-19 pandemic

Anna Rachel Conolly,
Jill Maben,
Ruth Abrams
et al.

Abstract: Using qualitative interview data (n = 142 interviews) generated with 50 nurses, over the course of the COVID-19 pandemic, this paper traces the trajectories of nurses in the UK and attempts to unpick the interplay between structure and agency in their narratives. Interviews were inductively analysed for themes and an additional narrative analysis was undertaken to preserve the form of each participant’s narrative. We argue that nurses’ pandemic trajectories occurred within the ‘psychological vulnerability-stig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…Moreover, nurses need to get behind and support such nurse leaders to engender change for the better. A UK qualitative study of 50 nurses throughout the COVID-19 pandemic concluded that some participants experienced marked psychological vulnerability and stigma due to non-supportive cultures and that management and organizations need to take responsibility for this (Conolly et al, 2024). What needs to happen is that the nursing profession must build collective resilience and cooperate across cultures and countries to pressure governments to invest in nursing.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Moreover, nurses need to get behind and support such nurse leaders to engender change for the better. A UK qualitative study of 50 nurses throughout the COVID-19 pandemic concluded that some participants experienced marked psychological vulnerability and stigma due to non-supportive cultures and that management and organizations need to take responsibility for this (Conolly et al, 2024). What needs to happen is that the nursing profession must build collective resilience and cooperate across cultures and countries to pressure governments to invest in nursing.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%